SPEAKING SKILLS IMPROVEMENT THROUGH TIME TOKEN ARENDS COOPERATIVE LEARNING MODEL IN CLASS IV STUDENTS IN SD INPRES 2 BANTAYA - Muhammad Aqil; Efendi Efendi; Ayu Andini (Jurnal Dikdas, 2020)
The problem in this study is the low speaking skills of students in Indonesian subjects. the objective of this research is to improve the speaking skills of IV grade students at SD Inpres 2 Bantaya through the time token arends learning model. This research is a classroom action research conducted in grade IV SD Inpres 2 Bantaya. Research subjects involved 20 students enrolled in the 2019/2020 school year. This study uses a Kemmis and Mc Taggart research design consists of two cycles. In each cycle held one meeting. the results showed pre-action test results of students who scored above the maximum completeness criteria (KKM) more than  75 only 4 students (16%), in the first cycle as many as 10 students scored above KKM (40%), and in the second cycle as many as 23 students got values above KKM (92%).